Melancholic celie in The Color Purple - Talif, Rosli; Sedehi, Kamelia Talebian (Universiti Putra Malaysia Press, 2014)
In her theory of the melancholic subject, Julia Kristeva asserts that the melancholic subject has a sense of loss, but she cannot share this feeling with others as she considers it as private. Although the melancholic subject is stranger to her mother tongue, she should use language to get rid of her sense of loss. In The Color Purple, Alice Walker devotes herself to the plight of black people’s lives in white society. She believes that the black feel a sense of loss as they are subject to racism, sexism and gender discrimination in white society. These black people, especially black women, should use language to express their sense of loss and deal with their traumatic experiences. This article intends to focus on Julia Kristeva’s melancholic subject and apply it to Alice Walker’s The Color Purple.